Increase in the degree of coexpression of myosin heavy chain isoforms in skeletal muscle fibers of the very old. - Andersen, J L; Terzis, G.; Kryger, A (Muscle Nerve, 1999)
Myosin heavy chain (MHC) isoform composition was determined in 2264 single skeletal muscle fibers from vastus lateralis muscle of a group (n = 12) of very old subjects (average age, 88 years). The number of fibers containing only MHC I, IIA, or IIX was 19.9%, 27.2%, and 0.3%, respectively. Surprisingly, 28.5% of the fibers displayed coexpression of both MHC I and IIA, a phenotype that is present in younger adults in very small percentages. Among these fibers coexpressing MHC I and IIA, the majority had a dominant expression of MHC I. Additionally, a small number of fibers coexpressing MHC I and IIX without any MHC IIA, and fibers co-expressing all three isoforms were observed. Altogether, 52.6% of all fibers examined in these very old subjects coexpressed two or three MHC isoforms. The present study provides evidence that advanced age leads to a significant elevation of skeletal muscle fibers displaying coexpression of two MHC isoforms and that a separation into slow and fast fibers in very old individuals may therefore be somewhat misleading. The clinical significance of the elevated number of fibers coexpressing MHC I and IIA is uncertain.
Keywords: Aged; Aged, 80 and over; Aging; Female; Humans; Male; Muscle Fibers, Skeletal; Muscle, Skeletal; Myosin Heavy Chains; Myosins